High-temperature-resistant bio-based polyamide as well as controllable polymerization method and application thereof

By performing solid phase increase, viscosity-condensation and polycondensation under vacuum gradient conditions, the problem of instability and high yellow index of high temperature-resistant nylon materials during polymerization was solved, and high temperature-resistant biomass with excellent mechanical properties and good color were prepared. Polyamide, suitable for a variety of industrial applications.

CN119463161AActive Publication Date: 2025-02-18INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411721219.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-18
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing high-temperature resistant nylon materials have problems of instability and high yellow index during the polymerization process, which affects the appearance and application of their finished products.

Method used

The solid phase increase, viscosity and polycondensation are carried out under the reduced vacuum gradient conditions by prepolymerization, controlling the controllable removal of small molecules of water during the polymerization process, and high temperature resistant bio-based polyamides are prepared.

Benefits of technology

The stability and color improvement of the polymerization process are achieved, the yellow index is reduced, and the mechanical properties of the obtained materials are excellent, which are suitable for the automotive industry, electronic appliances and mechanical manufacturing fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158079150000131
    Figure BDA0005158079150000131
Patent Text Reader

Abstract

The invention provides high-temperature-resistant bio-based polyamide as well as a controllable polymerization method and application thereof, and belongs to the technical field of bio-based high polymer materials. The preparation method comprises the following steps: mixing nylon salt with water, mixing an obtained nylon salt solution with an additive, and carrying out a prepolymerization reaction to obtain a nylon prepolymer; and under the condition of protective gas, carrying out solid-phase tackifying polycondensation on the nylon prepolymer under the condition of at least three sequentially reduced vacuum gradients to obtain the high-temperature-resistant bio-based polyamide, the nylon salt comprises bio-based nylon 5T salt, bio-based nylon 5I salt, bio-based nylon 52 salt, bio-based nylon 56 salt and bio-based nylon 510 salt. According to the invention, solid-phase tackifying polycondensation is carried out under the sequentially reduced vacuum gradient condition, controllable removal of small molecule water in the polymerization process is realized, formation of high-temperature-resistant bio-based polyamide with narrow molecular weight distribution, good color and excellent mechanical properties is facilitated, and the problems of unstable polyamide polymerization and high yellow index are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of bio-based polymer materials, and in particular to a high-temperature resistant bio-based polyamide and a controllable polymerization method and application thereof. Background Art

[0002] Polyamide, commonly known as nylon, is a special engineering plastic with excellent properties such as high temperature resistance, wear resistance, fatigue resistance, high strength, and high impact resistance. It is widely used in the automotive industry, electronic appliances, machinery manufacturing and other fields. Since the decomposition temperature of high temperature resistant nylon is lower than the melting point, the molding and processing of high temperature resistant nylon is a major problem. Therefore, in order to improve its processing stability, high temperature resistant nylon is generally copolymerized and modified to partially reduce the melting point of high temperature resistant nylon and achieve formability. Therefore, most commercialized high temperature resistant nylon materials are copolymerized and modified varieties.

[0003] At present, high temperature resistant nylon resin is basically prepared by petroleum-based monomer technology, such as synthetic monomers such as butanediamine, hexamethylenediamine and nonanediamine, which are all derived from petroleum. With the continuous development of the global economy, environmentally friendly materials have become the focus of public attention, and low-carbon and environmentally friendly new materials from bio-based materials are about to become the mainstream development trend.

[0004] 1,5-Pentamethylenediamine is a compound produced from the enzyme-catalyzed decarboxylation of lysine. Its raw materials come from renewable sugar-based biomass and it is a typical bio-based compound. However, due to the complexity and high cost of its biochemical synthesis method, it has not been paid attention to for a long time. In recent years, with the continuous maturity of the synthesis and preparation technology of pentamethylenediamine, its synthesis cost and purity have reached the level of petroleum-based nylon monomers such as hexamethylenediamine. Therefore, the development of bio-based high-temperature resistant nylon 5X based on pentamethylenediamine monomer has great practical significance for reducing carbon emissions.

[0005] At present, the industry mostly adopts a two-step method, i.e., prepolymerization followed by melting or solid phase thickening, to prepare high temperature resistant nylon. Melt thickening requires melting the prepolymer. Since high temperature resistant polyamide generally has a high melting point, the temperature of melt thickening is generally above 300°C. However, polyamide is very prone to various side reactions after exceeding 280°C, resulting in various color problems and black spot problems in high temperature resistant polyamide. Solid phase thickening is usually carried out at a temperature several tens of degrees below the melting point of the polymer, which basically eliminates the black spot problem. However, solid phase thickening requires a very high vacuum degree. At the same time, the equipment is generally in a rotating state, and the thickening time is generally long. It is difficult to ensure that there is absolutely no oxygen entering the system for a long time. Moreover, since high temperature resistant polyamide is generally in a powder state, it is also easy to block the vacuum pipeline in the vacuum system. The obtained high temperature nylon usually has a high yellow index, which affects the appearance of the final product and greatly limits its application.

[0006] At the same time, if nylon is exposed to moisture during the polymerization process, it may cause the nylon material to turn yellow. This yellowing is mainly due to the contact of nylon material with oxygen at high temperature, which causes the amide bond to break and decompose, forming colored peroxides, which in turn causes yellowing. In addition, nitrogen oxides (NO x ) will also cause oxidation of nylon amino groups and most hindered phenolic antioxidants, generating yellow quinone structures, leading to yellowing. Therefore, moisture control during the polymerization process is crucial to reducing the yellowing of nylon materials. Summary of the invention

[0007] The purpose of the present invention is to provide a high temperature resistant bio-based polyamide and a controllable polymerization method and application thereof, so as to solve the problems of unstable polymerization and high yellow index.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a controllable polymerization method of high temperature resistant bio-based polyamide, comprising the following steps:

[0010] mixing nylon salt with water, mixing the obtained nylon salt solution with an additive, and performing a prepolymerization reaction to obtain a nylon prepolymer;

[0011] Under protective gas conditions, subjecting the nylon prepolymer to solid phase viscosity-enhancing polycondensation under successively decreasing vacuum gradient conditions to obtain a high temperature resistant bio-based polyamide;

[0012] The successively decreasing vacuum gradients include at least three vacuum gradients;

[0013] The nylon salt includes one or more of bio-based nylon 5T salt, bio-based nylon 5I salt, bio-based nylon 52 salt, bio-based nylon 56 salt, and bio-based nylon 510 salt.

[0014] Preferably, the mass fraction of nylon salt in the nylon salt solution is 10 to 90%.

[0015] Preferably, the additives include at least one or more of a catalyst, an antioxidant, an antistatic agent, an anti-ultraviolet agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant, a lubricant, and a matting agent; the amount of the additives used is 0.01 to 1 wt.% of the total mass of the nylon salt solution.

[0016] Preferably, the prepolymerization reaction is carried out at a temperature of 200 to 240° C., a pressure of 1.5 to 2.3 MPa, and a time of 0.5 to 5 h.

[0017] Preferably, the protective gas includes one or more of nitrogen, argon and carbon dioxide.

[0018] Preferably, when the successively decreasing vacuum gradient includes three vacuum gradients, the three vacuum gradients are low vacuum, medium vacuum and high vacuum, the low vacuum is 101325~3000Pa, the medium vacuum is 3000~500Pa, and the high vacuum is 500~10Pa.

[0019] Preferably, the temperature of the solid phase viscosity-increasing polycondensation is 220-300° C., the time is 2-15 hours, and the stirring speed is 20-120 r / min.

[0020] The present invention provides a high-temperature resistant bio-based polyamide prepared by the controlled polymerization method described in the above technical solution, wherein the yellowness index of the high-temperature resistant bio-based polyamide is less than 15.

[0021] The present invention also provides application of the high temperature resistant bio-based polyamide in the automotive industry, electronic appliances or machine manufacturing fields.

[0022] Beneficial effects:

[0023] The present invention performs solid phase viscosity increasing polycondensation under successively decreasing vacuum gradient conditions. Under the vacuum state, the pressure of air and water vapor decreases, and the boiling point of water also decreases, making it easier to extract moisture from the system. The vacuum gradient decreases successively, which is convenient for strictly controlling the vacuuming time and process, ensuring the thoroughness and controllability of moisture removal, thereby achieving controllable removal of small molecule water during the polymerization process, which is beneficial to the formation of high temperature resistant bio-based polyamide with narrow molecular weight distribution, good color and excellent mechanical properties, and solves the problems of unstable polyamide polymerization and high yellow index.

[0024] The present invention adopts the method of prepolymerization and solid phase polymerization under successively decreasing vacuum gradients to prepare high temperature resistant bio-based polyamide. The polymerization time used is short and there is no vacuum pipeline blockage phenomenon, thereby avoiding the problems of generally long viscosity increase time, difficulty in ensuring that absolutely no oxygen enters the system for a long time, and high temperature resistant polyamide powder easily blocks vacuum pipelines in the vacuum system, resulting in poor product appearance. The yellow index of the obtained high temperature resistant polyamide is lower than 15, which greatly improves the quality of downstream engineering plastics, film products and fiber products, reduces the manufacturing cost, and has great industrialization prospects. The polyamide of the present invention can be formed into a desired shape by injection molding, film molding, melt spinning, blow molding, vacuum molding and other methods, and can be used in, for example, injection molded products, films, sheets, monofilaments, ribbons, fibers, etc., and can also be used in adhesives, coatings, etc.

[0025] Furthermore, the present invention can also reduce the fluctuation of the solution position and the probability of gel generation by limiting the concentration of the nylon salt solution, which is beneficial to the control of black spots. DETAILED DESCRIPTION

[0026] The present invention provides a controllable polymerization method of high temperature resistant bio-based polyamide, comprising the following steps:

[0027] mixing nylon salt with water, mixing the obtained nylon salt solution with an additive, and performing a prepolymerization reaction to obtain a nylon prepolymer;

[0028] Under protective gas conditions, subjecting the nylon prepolymer to solid phase viscosity-enhancing polycondensation under successively decreasing vacuum gradient conditions to obtain a high temperature resistant bio-based polyamide;

[0029] The successively decreasing vacuum gradients include at least three vacuum gradients;

[0030] The nylon salt includes one or more of bio-based nylon 5T salt, bio-based nylon 5I salt, bio-based nylon 52 salt, bio-based nylon 56 salt, and bio-based nylon 510 salt.

[0031] In the present invention, nylon salt and water are mixed, and the obtained nylon salt solution is subjected to a prepolymerization reaction to obtain a nylon prepolymer; the present invention has no special limitation on the preparation of nylon salt, and any preparation method known in the art can be used. In an embodiment of the present invention, the preparation method of the nylon salt is specifically as follows: under normal pressure and protective atmosphere conditions, the bio-based diacid is dissolved in a solvent at 50 to 100°C to prepare an acid solution with a mass fraction of 30 to 80%; the bio-based diamine is dissolved in the same solvent at 50 to 100°C to prepare an amine solution with a mass fraction of 30 to 80%; under stirring conditions of a speed of 200 to 300 r / min, the amine solution is added to the acid solution, the molar ratio of the amino group to the carboxyl group is 1 to 1.1:1, the temperature is maintained at 40 to 90°C, and stirring is continued for 0.5 to 2h, the obtained mixed solution is cooled to 0 to 20°C, and allowed to stand for 1 to 4h, crystallization is precipitated, and after filtering, washing, and drying, the bio-based nylon salt is obtained. The gas used for the protective atmosphere of the present invention is preferably at least one of nitrogen, argon, helium and carbon dioxide, more preferably at least one of nitrogen, argon and helium, and more preferably one of nitrogen and argon; the present invention has no limitation on the bio-based diacid and bio-based diamine, as long as the bio-based nylon salt can be prepared. In an embodiment of the present invention, the bio-based diacid is preferably one of terephthalic acid, isophthalic acid, adipic acid, oxalic acid or sebacic acid, and the bio-based diamine is preferably pentamethylenediamine; the solvent of the present invention is preferably pure water or anhydrous ethanol.

[0032] The present invention preferably puts nylon salt into a 20L stainless steel high-pressure reactor, adds water, replaces the air in the reactor with nitrogen for 5 times, and then stirs for 1 to 2 hours at 70 to 90°C and 0.5MPa protective atmosphere to completely dissolve the nylon salt, prepares a nylon salt solution, and performs a prepolymerization reaction.

[0033] In the present invention, the mass fraction of nylon salt in the nylon salt solution is preferably 10-90%, more preferably 20-80%, and more preferably 30-70%; adjusting the concentration of the nylon salt solution is beneficial to controlling black spots, because the fluctuation of the solution position is reduced, which reduces the probability of gel formation, but too high a concentration is not good for the stability of the oxygen-controlled solution, and when the concentration is too low, the energy consumption is high, the equipment utilization rate is low, and the concentrated liquid level difference is large, which is not conducive to black spot control.

[0034] In the present invention, the additive preferably includes at least one or more of a catalyst, an antioxidant, an antistatic agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant, and a matting agent, and further preferably includes a catalyst, an antioxidant and a capping agent. The amount of the additive is preferably 0.01 to 1 wt.% of the total mass of the nylon salt solution. Among them, the catalyst preferably includes anhydrous sodium hypophosphite, anhydrous potassium hypophosphite, anhydrous sodium phosphite and / or anhydrous potassium phosphite, etc.; the antioxidant preferably includes hindered phenol antioxidants (1010, 1076) and amine antioxidants (naphthylamine, diphenylamine); the antistatic agent preferably includes quaternary phosphonium salt type cationic antistatic agent, quaternary ammonium salt type cationic antistatic agent and / or alkyl sulfate type anionic antistatic agent, etc.; the weathering agent preferably includes hydroquinone compounds, benzotriazole compounds and / or benzophenone compounds; the end-capping agent preferably includes acetic acid, hexanoic acid, benzoic acid and / or hexylamine; the nucleating agent preferably includes inorganic particles such as silicon dioxide, clay, boron nitride and / or high melting point nylon, metal oxides, etc.; the flame retardant preferably includes magnesium hydroxide, brominated polystyrene, brominated polycarbonate and / or ammonium polyphosphate, etc.; the matting agent preferably includes inorganic substances such as titanium dioxide.

[0035] In the present invention, the prepolymerization reaction temperature is preferably 200-240° C., more preferably 220-240° C., the pressure is preferably 1.5-2.3 MPa, more preferably 1.7-2 MPa, and the time is preferably 0.5-5 h, more preferably 1-4 h.

[0036] In the present invention, after the prepolymerization reaction is completed, the pressure is reduced to 0.001 MPa, so that more than 98% of the water in the system is discharged, and the temperature is lowered and cooled to obtain a nylon prepolymer.

[0037] In the present invention, under protective gas conditions, nylon prepolymer is subjected to solid phase viscosity enhancement and polycondensation under successively decreasing vacuum gradient conditions to obtain high temperature resistant bio-based polyamide; the present invention preferably adds the nylon prepolymer into a solid phase viscosity enhancement device, firstly heats and stirs at 0.5 MPa to 240-270°C, reacts for 1-15 hours, opens a valve and slowly releases air for 1 hour to normal pressure, and then adopts a staged vacuum pumping method, each of which is maintained for 10-30 minutes under successively decreasing vacuum gradient conditions to obtain high temperature resistant bio-based polyamide; the present invention limits the pressure maintenance and heating to, on the one hand, making it easier to volatilize the gas and water vapor in the water by heating the water system by heating, so as to facilitate the subsequent removal of small molecule water by vacuum; on the other hand, it is to promote the accumulation of some small particles of nylon prepolymer during the heating process to avoid being sucked away by negative pressure and clogging the pipeline.

[0038] Before carrying out solid-phase viscosity enhancement and polycondensation, the present invention preferably replaces the solid-phase viscosity enhancement device with a protective gas. The protective gas replacement is preferably carried out by repeatedly evacuating the vacuum and then filling in the protective gas or by pressurizing the protective gas and then exhausting it to normal pressure. The protective gas preferably includes one or more of nitrogen, argon and carbon dioxide.

[0039] In the present invention, when the successively decreasing vacuum gradient includes three vacuum gradients, the three vacuum gradients are preferably low vacuum, medium vacuum and high vacuum; the low vacuum is preferably 101325~3000Pa, further preferably 8000~3000Pa, more preferably 5000~3000Pa, and the vacuum is expressed as an absolute pressure value; the medium vacuum is preferably 3000~500Pa, further preferably 2000~500Pa, more preferably 1000~500Pa, and the vacuum is expressed as an absolute pressure value; the high vacuum is preferably 500~10Pa, further preferably 100~10Pa, more preferably 50~10Pa, and the vacuum is expressed as an absolute pressure value.

[0040] In the present invention, the temperature of the solid phase viscosity increasing polycondensation is preferably 220-300° C., the time is preferably 2-15 h, the stirring speed is preferably 20-120 r / min, more preferably 40-100 r / min, and more preferably 50-80 r / min.

[0041] The present invention provides a high temperature resistant bio-based polyamide prepared by the controlled polymerization method described in the above technical solution. The yellowness index of the high temperature resistant bio-based polyamide is preferably less than 15, and further preferably less than 10.

[0042] The present invention also provides application of the high temperature resistant bio-based polyamide in the automotive industry, electronic appliances or machine manufacturing fields.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example 1

[0045] Under normal pressure and nitrogen purge conditions, 319.43 g of terephthalic acid was dissolved in pure water at 80° C. to obtain a turbid terephthalic acid suspension with a mass fraction of 60%; 203.17 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 40%; the clear pentamethylenediamine solution was added to the terephthalic acid solution at a speed of 300 r / min, the temperature was maintained at 80° C., and stirring was continued for 2 hours to obtain a mixed solution; the mixed solution was cooled to 10° C., allowed to stand for 3 hours, crystals were precipitated, and nylon 5T salt was obtained after filtering, washing and drying; according to the above reaction steps, nylon 56 salt was prepared using adipic acid and pentamethylenediamine as reaction monomers; A total of 951.45 g of dried nylon 5T salt and nylon 56 salt (molar ratio 1:1) were put into a 20L stainless steel autoclave, a certain mass of pure water was added to make the mass fraction of nylon salt 60%, and then 0.15wt.% of anhydrous sodium hypophosphite and 0.05wt.% of antioxidant 1010 were added, and the air in the autoclave was replaced with nitrogen for 5 times, and the nylon salt was completely dissolved by stirring at 80°C and 0.5MPa protective atmosphere for 1.5h; prepolymerization was carried out at 220°C and 1.7MPa for 2h, and then the pressure was reduced to 0.001MPa to discharge more than 98% of the water in the system, and the nylon 5T / 56 prepolymer was obtained after cooling;

[0046] Nylon 5T / 56 prepolymer was added into the solid phase viscosity increasing device, and the air in the kettle was replaced with nitrogen for 5 times. The mixture was first heated to 250°C at a speed of 50 r / min while maintaining a pressure of 0.5 MPa, and then reacted for 5 hours. The valve was opened and the air was slowly released for 1 hour to return to normal pressure. Then, a staged vacuuming method was adopted, and the vacuum degrees (absolute pressure values) were 80000Pa, 2000Pa and 100Pa respectively. The polymerization temperature was 250°C, and each was maintained for 10 minutes to obtain high temperature resistant bio-based polyamide.

[0047] Example 2

[0048] Under normal pressure and nitrogen purge conditions, 326.31 g of isophthalic acid was dissolved in pure water at 80°C to obtain a turbid isophthalic acid suspension with a mass fraction of 50%; 215.41 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 50%; the clear pentamethylenediamine solution was added to the isophthalic acid solution at a speed of 250 r / min, the temperature was maintained at 80°C, and stirring was continued for 2 hours to obtain a mixed solution; the mixed solution was cooled to 5°C, allowed to stand for 3 hours, crystals were precipitated, and nylon 5I salt was obtained after filtering, washing and drying; according to the above reaction steps, nylon 56 was prepared using adipic acid and pentamethylenediamine as reaction monomers. salt; a total of 966.14 g of dried nylon 5I salt and nylon 56 salt (molar ratio 1:1) were put into a 20L stainless steel autoclave, a certain mass of pure water was added to make the mass fraction of nylon salt 60%, and then 0.3wt.% of anhydrous sodium hypophosphite and 0.5wt.% of end-capping agent benzoic acid were added, and the air in the autoclave was replaced with nitrogen for 5 times, and the nylon salt was completely dissolved by stirring at 75°C and 0.5MPa protective atmosphere for 1.5h; prepolymerization was carried out at 230°C and 2MPa for 3h, and then the pressure was reduced to 0.001MPa to discharge more than 98% of the water in the system, and the nylon 5I / 56 prepolymer was obtained after cooling;

[0049] Nylon 5I / 56 prepolymer was added into the solid phase viscosity increasing device, and the air in the kettle was replaced with nitrogen for 5 times. The mixture was first heated to 260°C at a speed of 80r / min while maintaining a pressure of 0.5MPa, and then reacted for 2h. The valve was opened and the air was slowly released for 1h to return to normal pressure. Then, a staged vacuuming method was adopted with the vacuum degrees (absolute pressure values) of 10000Pa, 3000Pa and 400Pa respectively. The polymerization temperature was 260°C and maintained for 30min each to obtain high temperature resistant bio-based polyamide.

[0050] Example 3

[0051] Under normal pressure and argon purging conditions, 348.35 g of terephthalic acid was dissolved in pure water at 70° C. to obtain a turbid terephthalic acid suspension with a mass fraction of 50%; 226.78 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 50%; the clear pentamethylenediamine solution was added to the terephthalic acid solution at a speed of 200 r / min, the temperature was maintained at 70° C., and stirring was continued for 1 hour to obtain a mixed solution; the mixed solution was cooled to 10° C., allowed to stand for 4 hours, crystals were precipitated, and nylon 5T salt was obtained after filtering, washing and drying; according to the above reaction steps, nylon 5 was prepared using oxalic acid and pentamethylenediamine as reaction monomers. 2 salt; a total of 948.31 g of dried nylon 5T salt and nylon 52 salt (molar mass ratio of 1:1) were put into a 20L stainless steel high-pressure reactor, a certain mass of pure water was added to make the mass fraction of nylon salt 50%, and then 0.5wt.% of anhydrous sodium hypophosphite and 1wt.% of end-capping agent hexanoic acid were added, and argon gas replaced the air in the reactor 5 times, and stirred for 2h at 70°C and 0.5MPa protective atmosphere to completely dissolve the nylon salt; prepolymerization was carried out at 220°C and 1.8MPa for 1h, and then the pressure was reduced to 0.001MPa to discharge more than 98% of the water in the system, and the nylon 5T / 52 prepolymer was obtained after cooling;

[0052] Nylon 5T / 52 prepolymer was added to the solid phase viscosity increasing device, and the air in the kettle was replaced by argon for 5 times. The mixture was first heated to 250°C at a speed of 100 r / min while maintaining a pressure of 0.5 MPa, and then reacted for 8 hours. The valve was opened and the air was slowly released for 1 hour to return to normal pressure. Then, a staged vacuuming method was adopted with the vacuum degrees (absolute pressure values) of 6000 Pa, 1000 Pa and 100 Pa respectively. The polymerization temperature was 250°C and maintained for 10 minutes each to obtain high temperature resistant bio-based polyamide.

[0053] Example 4

[0054] Under normal pressure and argon purging conditions, 323.48 g of isophthalic acid was dissolved in pure water at 60°C to obtain a turbid isophthalic acid suspension with a mass fraction of 40%; 212.47 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 60%; then the clear pentamethylenediamine solution was added to the isophthalic acid solution at a speed of 300 r / min, the temperature was maintained at 60°C, and stirring was continued for 1 hour to obtain a mixed solution; the mixed solution was cooled to 15°C, allowed to stand for 3 hours, crystals were precipitated, filtered, washed and dried to obtain nylon 5I salt; according to the above reaction steps, oxalic acid and pentamethylenediamine were used as reaction monomers to obtain nylon 52 salt; a total of 963.52 g of dried nylon 5I salt and nylon 52 salt (molar mass ratio of 1:1) were put into a 20L stainless steel high-pressure reactor, a certain mass of pure water was added to make the mass fraction of nylon salt 80%, and then 0.01wt.% of anhydrous sodium hypophosphite and 0.1wt.% of antioxidant 1076 were added, and the air in the reactor was replaced by argon gas 5 times, and stirred at 90°C and 0.5MPa protective atmosphere for 1h to completely dissolve the nylon salt; prepolymerization was carried out at 210°C and 2.2MPa for 5h, and then the pressure was reduced to 0.001MPa to discharge more than 98% of the water in the system, and the nylon 5I / 52 prepolymer was obtained after cooling;

[0055] Nylon 5I / 52 prepolymer was added to the solid phase viscosity increasing device, and the air in the kettle was replaced by argon for 5 times. The mixture was first heated to 270°C at a speed of 120 r / min while maintaining a pressure of 0.5 MPa, and then reacted for 8 hours. The valve was opened and the air was slowly released for 1 hour to return to normal pressure. Then, a staged vacuuming method was adopted with the vacuum degrees (absolute pressure values) of 4000 Pa, 2000 Pa and 80 Pa respectively. The polymerization temperature was 270°C and maintained for 20 minutes each to obtain high temperature resistant bio-based polyamide.

[0056] Example 5

[0057] Under normal pressure and nitrogen purge conditions, 311.04 g of terephthalic acid was dissolved in pure water at 80°C to obtain a turbid terephthalic acid suspension with a mass fraction of 50%; 200.75 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 50%; then the clear pentamethylenediamine solution was added to the terephthalic acid solution at a speed of 200 r / min, the temperature was maintained at 80°C, and stirring was continued for 1 hour to obtain a mixed solution; the mixed solution was cooled to 10°C, allowed to stand for 2 hours, crystals were precipitated, filtered, washed and dried to obtain nylon 5T salt; according to the above reaction steps, sebacic acid and pentamethylenediamine were used as reaction monomers to obtain nylon 510 salt; a total of 962.81 g of dried nylon 5T salt and nylon 510 salt (molar mass ratio of 1:1) were put into a 20L stainless steel autoclave, a certain mass of pure water was added to make the mass fraction of nylon salt 70%, and then 0.3wt.% of anhydrous sodium hypophosphite and 0.1wt.% of antioxidant naphthylamine were added, and the air in the autoclave was replaced with nitrogen for 5 times, and the nylon salt was completely dissolved at 70°C and 0.5MPa under stirring for 2h; prepolymerization was carried out at 240°C and 2.3MPa for 0.5h, and then the pressure was reduced to 0.001MPa to discharge more than 98% of the water in the system, and the nylon 5T / 510 prepolymer was obtained after cooling;

[0058] Nylon 5T / 510 prepolymer was added into the solid phase viscosity increasing device, and the air in the kettle was replaced with nitrogen for 5 times. The mixture was first heated to 260°C at a speed of 40r / min while maintaining a pressure of 0.5MPa, and then reacted for 15h. The valve was opened and the air was slowly released for 1h to normal pressure. Then, a staged vacuuming method was adopted with the vacuum degrees (absolute pressure values) of 4000Pa, 800Pa and 100Pa respectively. The polymerization temperature was 260°C and maintained for 20min each to obtain high temperature resistant bio-based polyamide.

[0059] Example 6

[0060] Under normal pressure and nitrogen purge conditions, 304.82 g of isophthalic acid was dissolved in pure water at 70°C to obtain a turbid isophthalic acid suspension with a mass fraction of 60%; 197.48 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 40%; the clear pentamethylenediamine solution was added to the isophthalic acid solution at a speed of 200 r / min, the temperature was maintained at 70°C, and stirring was continued for 1 hour to obtain a mixed solution; the mixed solution was cooled to 10°C, allowed to stand for 4 hours, crystals were precipitated, filtered, washed and dried to obtain nylon 5I salt; according to the above reaction steps, sebacic acid and pentamethylenediamine were used as reaction monomers to obtain nylon 5 10 salt; 959.03 g of dried nylon 5I salt and nylon 510 salt (molar mass ratio 1:1) were put into a 20L stainless steel autoclave, a certain mass of pure water was added to make the mass fraction of nylon salt 50%, and then 0.4wt.% of anhydrous sodium hypophosphite and 0.6wt.% of end-capping agent hexylamine were added, and the air in the autoclave was replaced with nitrogen for 5 times, and the nylon salt was completely dissolved by stirring at 70°C and 0.5MPa protective atmosphere for 2h; prepolymerization was carried out at 220°C and 2.2MPa for 4h, and then the pressure was reduced to 0.001MPa to discharge more than 98% of the water in the system, and the nylon 5I / 510 prepolymer was obtained after cooling;

[0061] Nylon 5I / 510 prepolymer was added into the solid phase viscosity increasing device, and the air in the kettle was replaced with nitrogen for 5 times. The mixture was first heated to 260°C at a speed of 20r / min while maintaining a pressure of 0.5MPa, and then reacted for 8h. The valve was opened and the air was slowly released for 1h to return to normal pressure. Then, a staged vacuuming method was adopted with the vacuum degrees (absolute pressure values) of 5000Pa, 1000Pa and 10Pa respectively. The polymerization temperature was 260°C and maintained for 30min each to obtain high temperature resistant bio-based polyamide.

[0062] Example 7

[0063] Under normal pressure and nitrogen purge conditions, 341.07 g of terephthalic acid was dissolved in pure water at 50°C to obtain a turbid terephthalic acid suspension with a mass fraction of 40%; 219.20 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 60%; the clear pentamethylenediamine solution was added to the terephthalic acid solution at a speed of 300 r / min, the temperature was maintained at 50°C, and stirring was continued for 1 hour to obtain a mixed solution; the mixed solution was cooled to 20°C, allowed to stand for 2 hours, crystals precipitated, filtered, washed and dried to obtain nylon 5T salt; according to the above reaction steps, nylon 5I salt was prepared using isophthalic acid and pentamethylenediamine as reaction monomers; the dried nylon A total of 955.20 g of nylon 5T salt and nylon 5I salt (molar mass ratio of 1:1) were put into a 20L stainless steel high-pressure reactor, a certain mass of pure water was added to make the mass fraction of nylon salt 50%, and then 0.5 wt.% of anhydrous sodium hypophosphite, 0.09 wt.% of antioxidant diphenylamine and 0.8 wt.% of end-capping agent benzoic acid were added, and the air in the reactor was replaced with nitrogen for 5 times, and stirred for 2 hours at 70°C and 0.5 MPa protective atmosphere to completely dissolve the nylon salt; prepolymerization was carried out at 220°C and 1.5 MPa for 3 hours, and then the pressure was reduced to 0.001 MPa to discharge more than 98% of the water in the system, and the nylon 5T / 5I prepolymer was obtained after cooling;

[0064] Nylon 5T / 5I prepolymer was added into the solid phase viscosity increasing device, and the air in the kettle was replaced with nitrogen for 5 times. The mixture was first heated to 240°C at a speed of 100 r / min while maintaining a pressure of 0.5 MPa, and then reacted for 15 hours. The valve was opened and the air was slowly released for 1 hour to return to normal pressure. Then, a staged vacuuming method was adopted with the vacuum degrees (absolute pressure values) of 3000 Pa, 600 Pa and 20 Pa respectively. The polymerization temperature was 240°C and maintained for 20 minutes each to obtain high temperature resistant bio-based polyamide.

[0065] Example 8

[0066] Under normal pressure and carbon dioxide purge conditions, 310.29 g of terephthalic acid was dissolved in pure water at 80°C to obtain a turbid terephthalic acid suspension with a mass fraction of 50%; 204.28 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 50%; the clear pentamethylenediamine solution was added to the terephthalic acid solution at a speed of 300 r / min, the temperature was maintained at 80°C, and stirring was continued for 1 hour to obtain a mixed solution; the mixed solution was cooled to 10°C, allowed to stand for 4 hours, crystals were precipitated, filtered, washed and dried to obtain nylon 5T salt; the above reaction steps were operated with adipic acid and pentamethylenediamine as reaction monomers. Preparation of nylon 56 salt; 943.11 g of dried nylon 5T salt and nylon 56 salt (molar mass ratio 1:1) were put into a 20L stainless steel autoclave, a certain mass of pure water was added to make the mass fraction of nylon salt 80%, and then 0.7wt.% of anhydrous sodium hypophosphite was added, and carbon dioxide replaced the air in the autoclave 5 times, and stirred for 2 hours at 80°C and 0.5MPa protective atmosphere to completely dissolve the nylon salt; prepolymerization was carried out at 240°C and 2.2MPa for 1 hour, and then the pressure was reduced to 0.001MPa to discharge more than 98% of the water in the system, and the nylon 5T / 56 prepolymer was obtained after cooling;

[0067] Nylon 5T / 56 prepolymer was added into the solid phase viscosity increasing device, and the air in the kettle was replaced by carbon dioxide for 5 times. The mixture was heated to 240°C at a speed of 50 r / min while maintaining a pressure of 0.5 MPa, and then reacted for 10 hours. The valve was opened and the air was slowly released for 1 hour to return to normal pressure. Then, a staged vacuuming method was adopted with the vacuum degrees (absolute pressure values) of 3000 Pa, 500 Pa and 40 Pa respectively. The polymerization temperature was 240°C and maintained for 10 minutes each to obtain high temperature resistant bio-based polyamide.

[0068] Comparative Example 1

[0069] Under normal pressure and nitrogen purge conditions, 314.70 g of terephthalic acid was dissolved in pure water at 80°C to obtain a turbid terephthalic acid suspension with a mass fraction of 50%; 202.53 g of pentamethylenediamine was dissolved in pure water to obtain a clear pentamethylenediamine solution with a mass fraction of 50%; then the clear pentamethylenediamine solution was added to the terephthalic acid solution at a speed of 200 r / min, the temperature was maintained at 80°C, and stirring was continued for 1 hour to obtain a mixed solution; the mixed solution was cooled to 10°C, allowed to stand for 2 hours, crystals were precipitated, filtered, washed and dried to obtain nylon 5T salt; according to the above reaction steps, sebacic acid and pentamethylenediamine were used as reaction monomers to obtain nylon 510 salt; a total of 966.29 g of dried nylon 5T salt and nylon 510 salt (molar mass ratio of 1:1) were put into a 20L stainless steel autoclave, a certain mass of pure water was added to make the mass fraction of nylon salt 70%, and then 0.3wt.% of anhydrous sodium hypophosphite and 0.1wt.% of antioxidant naphthylamine were added, and the air in the autoclave was replaced with nitrogen for 5 times, and the nylon salt was completely dissolved by stirring at 70°C and 0.5MPa under a protective atmosphere for 2h; prepolymerization was carried out at 240°C and 2.3MPa for 0.5h, and then the pressure was reduced to 0.001MPa to discharge more than 98% of the water in the system, and the nylon 5T / 510 prepolymer was obtained after cooling;

[0070] Nylon 5T / 510 prepolymer was added into the solid phase viscosity increasing device, and the air in the kettle was replaced with nitrogen for 5 times. The mixture was heated to 260°C at a speed of 40r / min while maintaining a pressure of 0.5MPa, and then reacted for 15h. The valve was opened and the air was slowly released for 1h to return to normal pressure. Then, the vacuum degree (absolute pressure value) was 50Pa and the polymerization temperature was 260°C. The reaction was maintained for 20min to obtain high temperature resistant bio-based polyamide.

[0071] Performance Testing

[0072] The relative molecular weight (Mw), polydispersity index, relative viscosity, melting point, initial decomposition temperature, yellowness index and tensile strength of the high temperature resistant bio-based polyamides obtained in Examples 1 to 8 and Comparative Example 1 were measured, and the measurement results were recorded in Table 1. The measurement method used is as follows:

[0073] 1. Weight average molecular weight and polydispersity index

[0074] The molecular weight and distribution were tested by gel permeation chromatography (GPC), with hexafluoroisopropanol as the mobile phase and RI-UV as the detector;

[0075] 2. Relative viscosity

[0076] Weigh the dried high-temperature resistant bio-based polyamide and dissolve it in 96% concentrated sulfuric acid to prepare a solution with a mass concentration of 0.01 g / mL. Test the time it takes for the liquid to flow through the two scale lines of the glass ball of the Ubbelohde viscometer in a constant temperature water bath at 25±0.02°C. Repeat the measurement three times. The difference between the three measured values ​​is no more than 0.1s, and the average value is taken. The ratio of the outflow time t2 of the polyamide solution to the outflow time t1 of the pure solvent is the relative viscosity. The relative viscosity of the sample is calculated according to the formula η=t2 / t1.

[0077] 3. Melting point

[0078] Under the condition of nitrogen flow rate of 50mL / min, the temperature was raised from room temperature to 350℃ at a heating and cooling rate of 10℃ / min, kept constant for 3min, then dropped to room temperature, and then raised to 350℃. The endothermic peak temperature of the secondary melting curve was set as the melting point.

[0079] 4. Decomposition temperature

[0080] Under nitrogen conditions, the heating rate was 10 °C / min, the temperature was set from 30 °C to 800 °C, and the onset decomposition temperature was determined by thermogravimetric analysis (TGA);

[0081] 5. Yellow index

[0082] The yellow index is determined according to HG / T 3862-2006 method;

[0083] 6. Tensile properties

[0084] Under the conditions of temperature 25°C and relative humidity 75%, the tensile property test method is carried out according to the national standard GB / T 1040-2008, and the test speed is 50mm / min.

[0085] Table 1 Test results of high temperature resistant bio-based polyamides of Examples 1 to 8 and Comparative Example 1

[0086]

[0087] It can be seen from the above Examples 1 to 8 and Comparative Example 1 that the present invention provides a high temperature resistant bio-based polyamide, which adopts a staged vacuum pumping method to carry out solid phase viscosity enhancement and condensation polymerization on a nylon prepolymer, and the solid phase viscosity enhancement basically eliminates the black spot problem. The staged vacuum pumping method has a short polymerization time and no vacuum pipe blockage phenomenon, thereby achieving controllable removal of small molecule water during the polymerization process. The obtained high temperature resistant bio-based polyamide has a yellow index of less than 15, a narrow molecular weight distribution, good color, and excellent mechanical properties, which solves the problems of unstable polyamide polymerization and high yellow index, and makes it better applicable to the automotive industry, electronic appliances or machinery manufacturing fields.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A controlled polymerization method for high temperature resistant bio-based polyamide, characterized in that: The following steps are involved: Mixing nylon salt with water, mixing the obtained nylon salt solution with an additive, and performing a prepolymerization reaction to obtain a nylon prepolymer; Under protective gas conditions, subjecting the nylon prepolymer to solid phase viscosity-enhancing polycondensation under successively decreasing vacuum gradient conditions to obtain a high temperature resistant bio-based polyamide; The successively decreasing vacuum gradients include at least three vacuum gradients; The nylon salt includes one or more of bio-based nylon 5T salt, bio-based nylon 5I salt, bio-based nylon 52 salt, bio-based nylon 56 salt, and bio-based nylon 510 salt.

2. The controlled polymerization method according to claim 1, characterized in that: The mass fraction of nylon salt in the nylon salt solution is 10-90%.

3. The controlled polymerization method according to claim 1, characterized in that: The additives include at least one or more of a catalyst, an antioxidant, an antistatic agent, an anti-ultraviolet agent, a weathering agent, a capping agent, a nucleating agent, a flame retardant, a lubricant, and a matting agent; the amount of the additives is 0.01 to 1 wt.% of the total mass of the nylon salt solution.

4. The controlled polymerization method according to claim 1, characterized in that: The prepolymerization reaction is carried out at a temperature of 200 to 240° C., a pressure of 1.5 to 2.3 MPa, and a time of 0.5 to 5 hours.

5. The controlled polymerization method according to claim 1, characterized in that: The protective gas includes one or more of nitrogen, argon and carbon dioxide.

6. The controlled polymerization method according to claim 1, characterized in that: When the successively decreasing vacuum gradient includes three vacuum gradients, the three vacuum gradients are low vacuum, medium vacuum and high vacuum, the low vacuum is 101325-3000Pa, the medium vacuum is 3000-500Pa, and the high vacuum is 500-10Pa.

7. The controlled polymerization method according to claim 1, characterized in that: The temperature of the solid phase viscosity increasing polycondensation is 220-300° C., the time is 2-15 hours, and the stirring speed is 20-120 r / min.

8. The high temperature resistant bio-based polyamide prepared by the controlled polymerization method according to any one of claims 1 to 7, characterized in that: The yellowness index of the high temperature resistant bio-based polyamide is less than 15.

9. Use of the high temperature resistant bio-based polyamide according to claim 8 in the automotive industry, electronic appliances or machinery manufacturing fields.

Citation Information

Patent Citations

  • Process method for preparing nylon12 by taking long-chain amino acid as monomer

    CN107312170A

  • Preparation process of multifunctional semi-aromatic nylon

    CN116496489A

  • Controllable polymerization method of bio-based nylon 5X

    CN118515867A

  • Vacuum dryer for polymer-based consumables used in additive manufacturing

    US20230144511A1